If a = 3 units, b = 7 units, and c = 10 units, what is the volume of the three prisms above?a 210 cubic units
b 153 cubic units
c 180 cubic units
d 162 cubic units
elisaselmani9 avatar

Answers

Answer 1
Answer: First prism= 3*3*3= 27 cubic
Second prism= 7*3*3= 63 cubic
Third prism= 10*3*3= 90 cubic
You  add all three cubic together 27+63+90 and you get 180 cubic units
So C.180 cubic units is correct answer
Please mark me as ''The Brainliest Answer" please!!!!!!!!!!!

Related Questions

Alessandro wrote the quadratic equation –6 = x2 4x – 1 in standard form. what is the value of c in his new equation?
What’s the perimeter and area?
The first four terms of a sequence are 8, 12, 18, 27. Write a recursive function for this sequence.
PLEASE HELP I WILL GIVE EXTRA POINTS AND BRAINALIST to the first person
Simon lost 16 deliveries in August, 9 deliveries in September, and 6 deliveries in October. What integer would represent the loss of deliveries these three months?

What is the volume of the square pyramid with base edges 32 mm and slant height 34 mm?9,920 mm3


10,010 mm3


7,680 mm3


10,240 mm3

Answers

Answer:

The answer to your question is 10240 mm³

Step-by-step explanation:

Data

length of the base = 32 mm

length of the height = 34 mm

Formula

Volume of a pyramid = 1/3 x Area of the base x length of the height

Process

1.- Calculate the area of the base

Area = side x side

        = 32 x 32

        = 1024 mm²

2.- Find the height of the pyramid using the Pythagorean theorem

height² = 34² - 16²

height² = 1156 - 256

height² = 900

height = 30

3.- Calculate the volume of the pyramid

Volume = 1/3Area x height

             = 1/3(1024 x 30)

             = (30720)/3 mm³

             = 10240 mm³

Answer:

The answer is 5,940mm^3

Step-by-step explanation:

I got is right on my test

Help me solve the problem

Answers

{(1, 3), (2, 4), (3, 5), (4, 6), (5, 7)}

y = x + 2
the answer is 2. y=1x+2.

(hope this helps)

Solve the equation. If there is no solution, write no solution. 2|n| – 12 = 16

Answers

Add 12 to both sides

2|n| = 16 + 12

Simplify 16 + 12 to 28

2|n| = 28

Divide both sides by 2

|n| = 28/2

Simplify 28/2 to 14

|n| = 14

Break down the problem into these 2 equations

n = 14

-n = 14

Solve the 1st equation: n = 14

n = 14

Solve the 2nd equation: -n = 14

n = -14

When you collect all solutions;

n = ±14

Given a polynomial function f(x), describe the effects on the y-intercept, regions where the graph is increasing and decreasing, and the end behavior when the following changes are made. Make sure to account for even and odd functions.When f(x) becomes f(x) − 3
When f(x) becomes −2 ⋅ f(x)

Answers

First of all, let's review the definition of some concepts.


Even and odd functions:


A function is said to be even if its graph is symmetric with respect to they-axis, that is:


y=f(x) \ is \ \mathbf{even} \ if, \ for \ each \ x \ in \ the \ domain \ of \ f, \n f(-x)=f(x)


On the other hand, a function is said to be odd if its graph is symmetric with respect to the origin, that is:


y=f(x) \ is \ \mathbf{odd} \ if, \ for \ each \ x \ in \ the \ domain \ of \ f, \n f(-x)=-f(x)


Analyzing each question for each type of functions using examples of polynomial functions. Thus:



FOR EVEN FUNCTIONS:


1. Whenf(x)becomesf(x)-3 


1.1 Effects on the y-intercept


We need to find out the effects on the y-intercept when shifting the function f(x) into:


f(x)-3


We know that the graph f(x) intersects the y-axis when x=0, therefore:


y=f(0) \ is \ the \ y-intercept \ of \ f


So:


y=f(0)-3 \ is \ the \ new \ y-intercept


So the y-intercept of f(x)-3 is three units less than the y-intercept of f(x)


1.2. Effects on the regions where the graph is increasing and decreasing


Given that you are shifting the graph downward on the y-axis, there is no any effect on the intervals of the domain. The function f(x)-3 increases and decreases in the same intervals of f(x)


1.3 The end behavior when the following changes are made.


The function is shifted three units downward, so each point of f(x)-3 has the same x-coordinate but the output is three units less than the output of f(x). Thus, each point will be sketched as:



For \ y=f(x): \n P(x_(0),f(x_(0))) \n \n For \ y=f(x)-3: \n P(x_(0),f(x_(0))-3)



FOR ODD FUNCTIONS:


2. When f(x) becomes f(x)-3 


2.1 Effects on the y-intercept 


In this case happens the same as in the previous case. The new y-intercept is three units less. So the graph is shifted three units downward again.


An example is shown in Figure 1. The graph in blue is the function:


y=f(x)=x^3-x


and the function in red is:


y=f(x)-3=x^3-x-3


This function is odd, so you can see that:


y-intercept \ of \ f(x)=0 \n y-intercept \ of \ f(x)-3=-3


2.2. Effects on the regions where the graph is increasing and decreasing


The effects are the same just as in the previous case. So the new function increases and decreases in the same intervals of f(x)


In Figure 1 you can see that both functions increase and decrease at the same intervals.


2.3 The end behavior when the following changes are made.


It happens the same, the output is three units less than the output of f(x). So, you can write the points just as they were written before. 


So you can realize this concept by taking a point with the same x-coordinate of both graphs in Figure 1.


FOR EVEN FUNCTIONS:


3. When f(x) becomes -2.f(x) 


3.1 Effects on the y-intercept 


As we know the graph f(x) intersects the y-axis when x=0, therefore:


y=f(0) \ is \ the \ y-intercept \ again


And:


y=-2f(0) \ is \ the \ new \ y-intercept


So the new y-intercept is the negative of the previous intercept multiplied by 2.


3.2. Effects on the regions where the graph is increasing and decreasing


In the intervals when the function f(x) increases, the function -2f(x) decreases. On the other hand, in the intervals when the function f(x) decreases, the function -2f(x) increases. 


3.3 The end behavior when the following changes are made.


Each point of the function -2f(x) has the same x-coordinate just as the function f(x) and the y-coordinate is the negative of the previous coordinate multiplied by 2, that is:


For \ y=f(x): \n P(x_(0),f(x_(0))) \n \n For \ y=-2f(x): \n P(x_(0),-2f(x_(0)))



FOR ODD FUNCTIONS:


4. When f(x) becomes -2f(x) 


See example in Figure 2


y=f(x)=x^3-x


and the function in red is:


y=-2f(x)=-2(x^3-x)


4.1 Effects on the y-intercept 


In this case happens the same as in the previous case. The new y-intercept is the negative of the previous intercept multiplied by 2.


4.2. Effects on the regions where the graph is increasing and decreasing


In this case it happens the same. So in the intervals when the function f(x) increases, the function -2f(x) decreases. On the other hand, in the intervals when the function f(x) decreases, the function -2f(x) increases. 


4.3 The end behavior when the following changes are made.


Similarly, each point of the function -2f(x) has the same x-coordinate just as the function f(x) and the y-coordinate is the negative of the previous coordinate multiplied by 2.


The y-intercept of  is  .
Of course, it is 3 less than  , the y-intercept of  .
Subtracting 3 does not change either the regions where the graph is increasing and decreasing, or the end behavior. It just translates the graph 3 units down.
It does not matter is the function is odd or even.

 is the mirror image of  stretched along the y-direction.
The y-intercept, the value of  for  , is
which is  times the y-intercept of  .Because of the negative factor/mirror-like graph, the intervals where  increases are the intervals where  decreases, and vice versa.
The end behavior is similarly reversed.
If  then  .
If  then  .
If  then  .
The same goes for the other end, as  tends to  .
All of the above applies equally to any function, polynomial or not, odd, even, or neither odd not even.
Of course, if polynomial functions are understood to have a non-zero degree,  never happens for a polynomial function.
 

2 m3 of soil containing 35% sand was mixed into 6 m3 of soil containing 15% sand. what is the sand content of the mixture?

Answers

answer is: 1.6 m3 of sand

- 4 ( - 3ab + 4ad ) - 6 ( 4ab ) - ( - 3ad)

Answers

Answer:

Is this pure simplification? If it is, here you go. :)

Step-by-step explanation:

= 12ab - 16ad - 24ab + 3ad

= (12ab - 24ab) + (-16ad + 3ad)

= (-12ab) + (-13ad)

= -12ab - 13ad

Step-by-step explanation:

-4(-3ab +4ad) -6(4ab)-(-3ab)

12ab-16ad-24ab+3ad

12ab-24ab-16ad+3ad

-12ab -13ad

Other Questions